2013
DOI: 10.1124/dmd.112.049148
|View full text |Cite
|
Sign up to set email alerts
|

Tariquidar and Elacridar Are Dose-Dependently Transported by P-Glycoprotein and Bcrp at the Blood-Brain Barrier: A Small-Animal Positron Emission Tomography and In Vitro Study

Abstract: Elacridar (ELC) and tariquidar (TQD) are generally thought to be nontransported inhibitors of P-glycoprotein (Pgp) and breast cancer resistance protein (BCRP), but recent data indicate that they may also be substrates of these multidrug transporters (MDTs). The present study was designed to investigate potential transport of ELC and TQD by MDTs at the blood-brain barrier at tracer doses as used in positron emission tomography (PET) studies. We performed PET scans with carbon-11-labeled ELC and TQD before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
106
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 39 publications
11
106
0
Order By: Relevance
“…Similar observations have been made for other substrates of PGP and BCRP (de Vries et al, 2007;Chen et al, 2009;Polli et al, 2009). Furthermore, pretreatment of WT mice with 15 mg×kg 21 of the dual PGP and BCRP inhibitor tariquidar (Bankstahl et al, 2013) resulted in increased pilocarpine brain uptake to a degree comparable with PGP/ BCRP-deficient mice, underscoring that pilocarpine is indeed transported by both multidrug transporters. Interestingly, in Bcrp1 (2/2) mice we did not observe increased pilocarpine brain uptake, although in vitro results clearly show BCRP-mediated transport.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar observations have been made for other substrates of PGP and BCRP (de Vries et al, 2007;Chen et al, 2009;Polli et al, 2009). Furthermore, pretreatment of WT mice with 15 mg×kg 21 of the dual PGP and BCRP inhibitor tariquidar (Bankstahl et al, 2013) resulted in increased pilocarpine brain uptake to a degree comparable with PGP/ BCRP-deficient mice, underscoring that pilocarpine is indeed transported by both multidrug transporters. Interestingly, in Bcrp1 (2/2) mice we did not observe increased pilocarpine brain uptake, although in vitro results clearly show BCRP-mediated transport.…”
Section: Discussionsupporting
confidence: 77%
“…Again, this finding may be explained by a compensatory overexpression of other transporters in Bcrp1 (2/2) mice. In addition, many compounds interacting with multidrug transporters are described to behave dose dependently as both substrate and inhibitor (Bankstahl et al, 2013). Further studies are needed to determine whether this concept may be applicable for pilocarpine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, as previously demonstrated by us and others (Sasongko et al, 2005;Hsiao et al, 2008;Eyal et al, 2009Eyal et al, , 2010Muzi et al, 2009;Bauer et al, 2012;Mullauer et al, 2012;Bankstahl et al, 2013;Ke et al, 2013;Deo et al, 2014), when a drug is effluxed out of the brain, its concentration in the brain can be much lower than that in the plasma. This disconnect between tissue and plasma drug concentration will be modulated in the presence of a drug-drug interaction (DDI).…”
Section: Quantification Of Drug Transporters To Understand Interindivsupporting
confidence: 76%
“…Some tariquidar analogs with sulfonamide groups are P-gp specific, nevertheless tariquidar was toxic to healthy cells [107] . Since its discovery, tariquidar was described as non-competitive and non-transported inhibitor of P-gp [110] , while Bankstahl et al [111] have shown that tariquidar is concentration-dependently transported by P-gp. Recent transepithelial drug transport assays using radioactive tariquidar in human and mouse cell lines indicate that tariquidar functions as a high-affinity P-gp substrate rather than a non-competitive inhibitor [112] .…”
Section: Inhibition Of P-gpmentioning
confidence: 99%